2021
DOI: 10.1097/aln.0000000000003762
|View full text |Cite
|
Sign up to set email alerts
|

Individualized versus Fixed Positive End-expiratory Pressure for Intraoperative Mechanical Ventilation in Obese Patients: A Secondary Analysis

Abstract: Background General anesthesia may cause atelectasis and deterioration in oxygenation in obese patients. The authors hypothesized that individualized positive end-expiratory pressure (PEEP) improves intraoperative oxygenation and ventilation distribution compared to fixed PEEP. Methods This secondary analysis included all obese patients recruited at University Hospital of Leipzig from the multicenter Protective Intraoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 44 publications
1
40
1
Order By: Relevance
“…We also excluded 1 article after sensitivity analysis. Finally, 23 RCTs were included ( 12 , 20 41 ), which involved a total of 3,364patients with obesity who were randomized to 13 ventilation strategies ( Figure 1 ). Information extracted from each article included the first author, publication year, design of the study, surgery type, patient data (age, country, American Society of Anesthesiologists physical status classification [ASA], BMI and sample size), ventilation strategy, outcome measures (PaO2/FiO2, intraoperative lung compliance, postoperative pulmonary atelectasis) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also excluded 1 article after sensitivity analysis. Finally, 23 RCTs were included ( 12 , 20 41 ), which involved a total of 3,364patients with obesity who were randomized to 13 ventilation strategies ( Figure 1 ). Information extracted from each article included the first author, publication year, design of the study, surgery type, patient data (age, country, American Society of Anesthesiologists physical status classification [ASA], BMI and sample size), ventilation strategy, outcome measures (PaO2/FiO2, intraoperative lung compliance, postoperative pulmonary atelectasis) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In summary, 1 study ( 42 ) was assessed as having a high bias risk and was excluded. Two studies were assessed as being unclear ( 33 , 35 ), and the rest deemed to be low risk ( 12 , 20 32 , 34 , 36 41 ). All studies were symmetrically distributed within the funnel plot, indicating no publication bias (supporting information Figures S9–S11 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to lower elastance of the respiratory system and consecutively improves oxygenation during surgery [28,30,31]. Many authors have advocated the individualization of PEEP in the operating room [32,33], and there is recent evidence that individualized PEEP is superior to a standardized "one PEEP fits all" strategy, even if higher PEEP levels are routinely used [7]. The optimal method for the choice of best PEEP during mechanical ventilation in the operating room is, however, less clear [34].…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that an individualized PEEP (PEEP IND ) titration using electric impedance tomography (EIT) in obese patients resulted in a PEEP range of 10-26 cm H 2 O with a median of 18 cm H 2 O when selecting PEEP according to the lowest temporal inhomogeneity determined by the regional ventilatory delay (RVD I method) [6]. The comparison with a subgroup of patients of the large PROBESE trial comparing standard higher PEEP of 12 cm H 2 O vs. PEEP of 4 cm H 2 O suggested that lung recruitment was incomplete in both arms of the PROBESE trial [7]. Likewise, even in non-obese patients, the PEEP IND determined by EIT was found as high as median of 14 cm H 2 O (median, range of 8-20 cm H 2 O) [4].…”
Section: Introductionmentioning
confidence: 99%